Preconsolidation stress of gibbsitic and kaolinitic Oxisols under a multipractice conservationist coffee system - Carducci, Carla Eloize; de Oliveira, Geraldo César; Zeviani, Walmes Marques; Laureano, Henrique Aparecido; Barbosa, Samara Martins [UNESP]; Severiano, Eduardo da Costa; Curi, Nilton (Universidade Estadual de Londrina, 2021)
Our goal was to analyze the impact of a multipractice soil conservationist system on coffee production in tropical soils (LATOSSOLO VERMELHO-AMARELO caulinítico/kaolinitic Haplustox and LATOSSOLO VERMELHO-gibbsítico/gibbsitic Acrustox) in Minas Gerais, Brazil. In the experimental area, the soil management involved a set of multiple conservationist practices during cultivation for more than 3.5 yrs. Soil samples were collected at 0-5, 10-15, and 20-25 cm depths at two positions: planting rows and between rows. The soil physical and mechanical properties were determined, with a focus mainly on the preconsolidation stress model (preconsolidation stress versus matric tension). For the purpose of analysis, a split-split plot experimental design was implemented. A linear mixed regression model (LMR) was fitted, and Wald’s test was performed (P < 0.05). An improvement of soil physical quality for both Oxisols was observed at the planting row position. The effects of multipractice soil management after 3.5 yrs of cultivation in association with increased gibbsite content could promote new soil structure organization, as revealed by LMR, resulting in more resilient soils (between rows) and increasing the resistance to external pressures on gibbsitic Acrustox. Overall, the findings herein are in concordance with global trends towards conservationist practices that may alleviate soil compaction in agricultural systems to maintain environmental sustainability.
Pressão de pré-consolidação de Latossolos gibbsítico e caulinítico sob sistema de multipraticas conservacionista no cultivo cafeeiro
Keywords: Agricultural gypsum; Gibbsite; Kaolinite; Linear mixed regression model; Soil compaction